Поняття та особливості зміни підстави позову в цивільному судочинств - Пуль, С. І.; Pul, S. I. (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 2 (69). - С. 226-234., 2015)
Визначено і проаналізовано поняття, а також наведено особливості зміни підстави позову в цивільному судочинстві. З’ясовано, що зміна підстави позову є можливою, якщо у процесі розгляду справи встановлюється невідповідність між фактами, що обґрунтовують позов, і обставинами, за якими така вимога може бути задоволена. Визначено особливості заміни та уточнення підстави позову.

The concept of changing the reason of a claim in civil proceedings is defined and analyzed; its features are presented. It is proved that one of the signs of dispositive principle in civil proceedings is that the parties freely dispose granted to them procedural rights, with the assistance of which they can influence the process. Thus, the plaintiff has the right to increase or decrease the size of the claim, reject the claim, change the reason or the object of the claim. In turn, the defendant can acknowledge the claim fully or in part, or apply a counter-claim. The parties also have the right to enter into a settlement agreement. These rights of the parties arise from the general discretionary rule that each person who applied for a judicial protection may manage requirements at his/her own discretion, without violating the rights and legitimate interests of others. Taking into account the above stated, solving theoretical and practical aspects of the issue of changing the claim, its elements, namely the reason, is one of the most urgent in the science of civil procedure because further development of civil procedure is associated with the expansion of discretionary foundations. It is found out that under changing the reason of the claim we should understand the change of its actual part that is the actual reason. At the same time changing the legal basis of the claim does not cause the change of the claim, but its replacement with another claim because of the violation under such replacement of the inner identity of the first. In general the change of the bases of the claim is possible if in the process of the case we establish discrepancy between the facts that ground the claim and the circumstances under which such a requirement may be satisfied, and thus, changing the reason of the claim means that instead of legal facts, which ground the claim, new facts are set out. As soon as under the specification of the claim’s reason we refer to its addition with legal facts (i.e. increase) or exclusion of some from the facts stated by the plaintiff in the beginning (i.e. reduction), then this kind of change of the reason of the claim can be defined as quantitative. Unlike the specification the change of the original reason of the claim by another reason means its quality change, which is possible only in the claims with alternative basis.

Определено и проанализировано понятие, а также приведены особенности изменения основания иска в гражданском судопроизводстве. Установлено, что изменение основания иска возможно, если в процессе рассмотрения дела устанавливается несоответствие между фактами, обосновывающими иск, и обстоятельствами, по которым такое требование может быть удовлетворено. Определены особенности замены и уточнения основания иска.
Pul, S.I. (2015), “The concept and features of changing the reason of a claim in civil proceedings”, [“Poniattia ta osoblyvosti zminy pidstavy pozovu v tsyvilnomu sudochynstvi”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 226-234.
Пуль, С.И. Поняття та особливості зміни підстави позову в цивільному судочинстві // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 2 (69). - С. 226-234.
Keywords: Цивільно-процесуальне право. Civil and Procedure Law. Гражданское процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; позов; елементи позову; підстава позову; зміна підстави позову; принцип диспозитивності; позивач; докази; claim; elements of a claim; reason of a claim; changing the reason of a claim; principle of discretionary; plaintiff; evidence; иск; элементы иска; основание иска; изменение основания иска; принцип диспозитивности; истец; доказательства